Unexpected spaces of confinement: aversive technologies, intellectual disability, and “bare life” - Adams, Deanna L. (Punishment & society, 2017)
Giorgio Agamben describes the “camp” as the “zone of indistinction between law and violence” where bodies located in exceptional spaces are stripped of citizenship rights and embody “bare life.” We deploy Agamben’s analysis to the context of the everyday violence of aversive technologies meted out against students living at the dangerous intersections of race, class, gender, and disability and located in unexpected spaces of confinement such as schools, developmental centers, and family homes. We argue here that the logic of the “state of exception” applies to disabled children and adults where acts of violence enacted via disciplinary practices are justified as being outside the realm of the legal and subject to sovereign power. The locus of our study is the Judge Rothenberg Center that over the past 40 years has utilized behavioral techniques that have been investigated as abusive and only very recently has been held accountable for these infractions. We examine the discourses used to justify these forms of inhumane punishment as well as the discourses that oppose them to foreground the real material implications of “how we understand the role of systems and institutions of punishment” in unexpected spaces of confinement of children/adults with intellectual disabilities.